열탕 가열 중 한우 홍두깨살 및 아롱사태의 중심온도가 가열감량, 보수력, 표면색도 및 조직감에 미치는 영향 - 문윤희(Yoon-Hee Moon) (東아시아食生活學會誌, 2013)
In this experiment, the effect of internal temperature on the physical properties of Hanwoo beef eye of round (ER) and center of heel (CH) during boiling was investigated. The pH value of Hanwoo beef ER and CH began to increase significantly (p<0.05) compared to raw meat around an internal temperature of $40^{°}C$ and $50^{°}C$, respectively; in addition, it showed the biggest changes around $70^{°}C$ and $80^{°}C$, respectively. No significant difference beyond the temperatures noted above was observed. The $L^*$ value of Hanwoo beef ER and CH began to increase significantly around an internal temperature of $50^{°}C$ and $60^{°}C$, respectively, while the $a^*$ and $b^*$ values kept decreasing up to $80^{°}C$ (p<0.05). None of these values showed a significant difference beyond the threshold temperature ($50{\sim}60^{°}C$ for the $L^*$ value, $80^{°}C$ for the $a^*$ and $b^*$ values). Hanwoo beef ER and CH showed the highest cooking loss and lowest water holding capacity around an internal temperature of $60^{°}C$ and $70^{°}C$, respectively. No significant difference was observed beyond those temperatures. The hardness, gumminess and chewiness of Hanwoo beef ER and CH showed the biggest change around an internal temperature of $70^{°}C$ and $80^{°}C$, respectively, while their cohesiveness showed the biggest change around $60^{°}C$ and $70^{°}C$, respectively. No significant difference was observed beyond those temperatures. The springiness of Hanwoo beef ER and CH shown began to increase significantly around an internal temperature of $70^{°}C$ and $80^{°}C$, respectively, while it began to decrease significantly around $90^{°}C$ (p<0.05). Hanwoo beef ER showed a faster change in its physical properties due to boiling compared to CH. 한우의 홍두깨살과 아롱사태를 열탕에서 가열하는 동안 중심온도에 따른 물리적 특성 변화를 확인하였다. 홍두깨살과 아롱사태의 pH 값은 각각 중심온도 $40^{°}C$ 및 $50^{°}C$에서 생육의 pH 값보다 유의적(p<0.05)으로 상승하기 시작하여 각각 $70^{°}C$ 및 $80^{°}C$에서 가장 크게 변화한 후, 그 이상의 온도에서는 유의적 차이를 나타나지 않았다. 홍두깨살과 아롱사태의 표면색도에서 $L^*$값은 각각 $50^{°}C$ 및 $60^{°}C$까지 유의적으로 높아졌으나, $a^*$값 및 $b^*$값은 모두 $80^{°}C$까지 낮아졌으며 (p<0.05), 모두 그 이상의 온도에서는 유의적 차이가 없었다. 홍두깨살과 아롱사태의 중심온도가 각각 $60^{°}C$ 및 $70^{°}C$에서 가열감량이 가장 높은 반면 보수력은 가장 낮게 나타났으며, 그 이상의 온도에서는 유의적 차이를 보이지 않았다. 홍두깨살과 아롱사태의 조직감에서 경도, 뭉침성 및 저작성은 각각 $70^{°}C$ 및 $80^{°}C$에서 가장 크게 변하고, 응집성은 각각 $60^{°}C$ 및 $70^{°}C$에서 가장 크게 변하였으며, 그 이상의 온도에서는 유의적 차이를 나타나지 않았다. 탄력성은 홍두깨살과 아롱사태의 중심온도가 각각 $70^{°}C$ 및 $80^{°}C$에서 유의적으로 높아진 후두 부위 모두 $90^{°}C$부터 유의적으로 낮아졌다(p<0.05). 홍두깨살은 아롱사태보다 가열에 의한 물리적 특성 변화가 빠르게 나타났다.